Queer theory: an introduction - Jagose, Annamarie (New York University Press, 1996)
The essential history of queer theory The reclamation of the term queer over the last several decades marked a shift in the study of sexuality from a focus on supposedly essential categories such as gay and lesbian, to more fluid notions of sexual identity. On the cutting-edge of this significant shift was Annamarie Jagose’s classic text Queer Theory: An Introduction. In this groundbreaking work, Jagose provides a clear and concise explanation of queer theory, tracing it as part of an intriguing history of same-sex love over the last century. Blending insights from prominent theorists such as Judith Butler and David Halperin, Jagose illustrates that queer theory's challenge is to create new ways of thinking, not only about fixed sexual identities such as straight and gay, but about other supposedly immovable notions such as sexuality and gender, and man and woman. First released almost 25 years ago, this groundbreaking work has provided a foundation for the continuing evolution of queer theory in the twenty-first century.
Section: 153 pages ; 23 cm
Keywords: approches et analyses; cours; discipline; histoire; premier cycle; queer; sciences humaines; soc2014; thématiques

Feminist theorists: Three centuries of women's intellectual traditions - Spender, Dale (Women's Press, 1996)
Feminism was not born in 1968. Yet the work of three centuries of feminist thinkers has been dismissed, distorted or forgotten. Even the names of many of them remain unfamiliar, and few have so much as a mention in history books. Feminist Theorists demonstrates once and for all that we can no longer be content with received ideas about 'progress', which may explain the world for men, but which fail to make sense of the historical experience of women. It shows too that contemporary women have a rich intellectual tradition on which to draw for stimulus, inspiration and enjoyment.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire et politique; justice sociale; mouvements féministes; premier cycle; sciences humaines; thématiques; théories féministes